Penggunaan Media Canva Dalam Pengenalan Power Point Dalam Proses Belajar Mengajar Di SMA Negeri 1 Kutalimbaru - Fenty Debora Napitupulu; Yuni Sihombing; Desi Monalisa Hutapea; Wita Friska; Jojor Julprika Veronika Tambunan (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Community service (PkM) is an activity carried out by FKIP students at HKBP Nommensen University, Medan, together with their supervisors, which aims to develop students in increasing their abilities and independence in society. The application of the Canva application is a platform that can design graphics, visual and audio themes that are used by students to design learning, especially in writing, increase digital literacy and creativity, design photos, posters, logos, banners with the available features. The Canva application is very easy to use and can be accessed via an application downloaded on a device or laptop and can also be accessed via the official website which students can use during learning training activities which can provide ideas and motivation in literacy-based learning which is used to be carried out. training for students at SMA Negeri 1 Kutalimbaru in increasing digital literacy and learning creativity through the use of the Canva application. Based on the results of implementing community service, the author concludes that the Pkm activities went well and received a good response from the Kutalimbaru State High School so that students were able to use the Canva application media so that students were more active in the learning process.